Business Design And Implementation In PT Karya Bumi Pachingka (Industrial Solar Distribution Business) - Difa Pachingka, Haryo; Hasin, Al (International Journal of Education, Vocational and Social Science, 2025)
This study aims to design business development strategies for PT. Karya Bumi Pachingka, a distributor of industrial solar fuel in West Kalimantan. Utilizing SWOT analysis based internal and external analyses, this research identifies key challenges such as delivery delays due to inadequate infrastructure and suboptimal marketing strategies. On the other hand, significant opportunities are found in the increasing demand for industrial fuel and government policies promoting the use of sustainable energy, such as B30. This study provides recommendations for short-term and long-term strategies to enhance operational efficiency, expand market share, and develop sustainable products. These strategies include optimizing logistics processes to improve delivery efficiency, diversifying products to create added value, and expanding operational areas supported by strategic partnerships. By implementing these strategies, PT. Karya Bumi Pachingka is expected to overcome operational challenges, increase competitiveness, and become a leading player in the increasingly competitive industrial fuel market.